The Kreutzer sonata and other stories - Tolstoy, Leo, graf, 1828-1910. ([Place of publication not identified] : Floating Press, 2010)
The title novella in this collection of stories from literary master Leo Tolstoy, The Kreutzer Sonata, unleashed a firestorm of controversy upon its original publication. The story seeks to unpack the complex relationship between sex and love, and in it, Tolstoy makes a number of arguments about intimacy that were considered shocking in the context of nineteenth-century morals and mores. This collection is a wonderful introduction to Tolstoy's work for new readers, or for confirmed fans looking for some of Tolstoy's lesser-known works.
Chapter VIIIChapter IX; Chapter X; Chapter XI; Chapter XII; A Lost Opportunity; ""Polikushka"" -- Or, The Lot of a Wicked Court Servant; Chapter I; Chapter II; Chapter III; Chapter IV; Chapter V; Chapter VI; The Candle; Endnotes.
Added to collection customer.56279.3
Keywords: Tolstoy, Leo, -- graf, -- 1828-1910 -- Translations into English; Tolstoy, Leo, -- graf, -- 1828-1910; Short stories; Nouvelles; short stories; FICTION -- General; Short stories; Sociology & Social History; Social Sciences; Social Conditions; Translations